Comparative anatomical and transcriptomic analyses of the color variation of leaves in Aquilaria sinensis - Jiaqi Gao; Tong Chen; Chao Jiang; Tielin Wang; Ou Huang; Xiang Zhang; Juan Liu (PeerJ, 2021)
Color variation in plant tissues is a common phenomenon accompanied with a series of biological changes. In this study, a special-phenotype Aquilaria sinensis (GS) with color variation of leaf was firstly reported, and DNA barcode sequences showed GS samples could not be discriminated clearly with the normal A. sinensis sample (NS), which suggested that the variety was not the cause of the GS formation. To reveal the characteristics of GS compared to NS, the anatomical and transcriptome sequencing studies were carried out. In microscopic observation, the leaves of golden-vein-leaf sample (LGS) and normal-vein-leaf sample (LNS) showed significant differences including the area of the included phloem in midrib and the thickness parameters of palisade and spongy tissues; the stems of golden-vein-leaf sample (SGS) and normal-vein-leaf sample (SNS) were also different in many aspects such as the area of vessels and included phloem. In addition, the structure of chloroplast was more complete in the midrib of LNS than that of LGS, and some particles suspected as virus were found through transmission electron microscope as well. Genes upregulated in LGS in contrast with LNS were mainly enriched in photosynthesis. As for stems, most of the genes upregulated in SGS compared to SNS were involved in translation and metabolism processes. The pathways about photosynthesis and chlorophyll metabolism as well as some important transcription factors may explain the molecular mechanism of the unique phenotypes of leaves and the genes related to suberin biosynthesis may result in the difference of stems. In addition, the genes about defense response especially biotic stress associated with numerous pathogenesis-related (PR) genes upregulated in LGS compared to LNS indicated that the pathogen may be the internal factor. Taken together, our results reveal the macro- and micro-phenotype variations as well as gene expression profiles between GS and NS, which could provide valuable clues for elucidating the mechanism of the color variation of Aquilaria.